Link the Dots: Pesantren University, Islamization, and Recruitment - A Farid Saifuddin; M Faqih Nidzom; Nurita Juhdi; M Kholid Muslih; Usmanul Khakim (Universitas Darussalam Gontor, 2024)
This study aims to describe the relationship (link the dots) between Islamization, Pesantren Universities and Recruitment; the case of University ofDarussalam (UNIDA Gontor). The method used is Prospective Case Study. There are five steps of the case study, namely: data collection, data reduction, data display and conclusions. This study has described the link between the three dots: Pesantren University (UNIDA Gontor), Islamization, and recruitment. The finding is recruitment as a gateway in selecting the best candidates to realize UNIDA's vision of Islamization. It can be concluded that the position of recruitment within the framework of a pesantren university has been described. In addition, this study also has various limitations including 1) this study has not described recruitment practices at UNIDA Gontor. 2) This study has not yet reached a detailed explanation of recruitment rules based on the vision of the Islamization of Contemporary Knowledge.